Study the Effect of Welding Parameters during TIG Welding of Aluminum Plate and its Optimization - Pradeep Kumar Pradhan; Smarajit Punyakanti (International Journal of Engineering and Management Research, 2019)
Aluminium has very unique properties of light weight and corrosion resistance and due to this it becomes very interesting metal in the field of engineering. Mainly this paper deals with effect and optimization of certain range of values of process parameters during TIG welding of aluminium alloy 7075. In the first cycle of experiment the effect of values (in wide range) of gas flow rate and welding current during TIG welding of Aluminium alloy 7075 has been found out on its mechanical properties such as ultimate tensile strength and hardness. Visual inspection and dye penetrate test also has been performed for every sample of welding. From the results for ultimate tensile strength obtained in first cycle of experiment, a try has been made to optimize process parameters in second cycle of experiment by narrowing the range of values of gas flow rate and welding current. Finally the near optimal values of gas flow rate and welding current has been found to get maximum UTS.